Optimizing treatments for recurrent or metastatic head and neck squamous cell carcinoma. Issue 9 (2nd September 2018) - Specenier, Pol; Vermorken, Jan B
ABSTRACT: Introduction : The majority of patients with locally advanced head and neck squamous cell carcinoma (HNSCC) will recur. The treatment of patients with recurrent/metastatic (R/M HNSCC) is rapidly evolving. Areas covered : This article will comprehensively review the current systemic treatment of R/M HNSCC. Expert commentary : For the time being, the EXTREME regimen (cetuximab in combination with platinum and 5-fluorouracil) still remains standard of care in previously untreated R/M HNSCC patients who are candidates for combination chemotherapy. Single agents with well documented activity in HNSCC include methotrexate, cisplatin, 5-FU, docetaxel, and paclitaxel. The anti-PD-1 monoclonal antibody nivolumab can be considered the current standard of care in patients with R/M HNSCC progressing after platinum-based therapy based on the results of CheckMate 141 showing a survival benefit over standard of care drugs, such as single agent weekly cetuximab, methotrexate, or docetaxel. Multiple randomized phase III trials comparing anti-PD(L)-antibodies either as single agent or in combination with chemotherapy or an anti-CTLA-4 with the EXTREME as fist line treatment are ongoing or planned. The outcome of these trials might change the current treatment paradigm in previously untreated R/M HNSCC. Immunotherapeutic agents under active investigation include Toll-like receptor 8 agonists and inhibitors of IDO1.